PENGARUH RASIO KEUANGAN TERHADAP FINANCIAL REPORT FRAUD PADA PERUSAHAAN SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2022-2024 - Natasya Novelyn Br. Sihaloho; Amran Manurung; Manatap Berliana Lumbangaol (POLITEKNIK LP3I JAKARTA, 2026)
Financial statements represent a company’s financial transactions within a specific accounting period, providing information on operational performance. However, in reality, companies may fail to achieve their predetermined targets. Fraudulent practices often occur when management deliberately manipulates financial statement data to present misleading performance in order to attract investors and meet market expectations. In this context, financial ratios are widely used as analytical tools to detect financial report fraud in financial statements. This study aims to analyze the effect of financial ratios on financial report fraud in food and beverage sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The independent variables used in this study are WCTA, DAR, and ROA, while the dependent variable is financial report fraud measured using the Altman Z-Score. This study employs a quantitative approach with multiple linear regression analysis. The sample was selected using a purposive sampling technique, resulting in 90 observations after data processing. The results indicate that partially, Working Capital to Total Assets (WCTA) and Return on Assets (ROA) have a positive and significant effect on financial report fraud, while Debt to Asset Ratio (DAR) has a negative and significant effect on financial report fraud.